PENINGKATAN DERAJAT PUTIH TEPUNG UMBI SUWEG (Amorpophalus oncophilus) DENGAN KOMBINASI PROSES BLANCHING DAN BLEACHING MENGGUNAKAN LARUTAN SODIUM METABISULFIT - M. Khoiron Ferdiansyah; Endang Is Retnowati; Iffah Muflihati; Arief R. Affandi (Jurnal Pangan dan Gizi, 2015)
Suweg is one of carbohydrate source that has low glycemic index. This kind of tuber can be made into a flour that has some specific physicochemical characteristic and used in bakery, cake, and bread product. The Suweg flour has a darker colour than other flour. Such a disadvantage for some food processing because it can altered the quality of food product. The aim of this research was to analyze the influence (effect) of blanching and bleaching process on the degree of whiteness of Suweg flour. The experiment design on this research was using factorial design with 3 combination variable, there are with/without blanching, sodium metabisulphite concentration, and length of soaking. The result indicated a significant effect of bleaching with sodium metabisulphite but not using blanching process. Blanching process made the flour colour became darker than raw Suweg flour. The biggest value of whiteness index, L 84.23 was found at flour that processed with sodium metabisulphite 4% and 3 hours of soaking.Keywords : suweg, whiteness index, blanching, bleaching